Valores da Amplitude de Distribuição do Tamanho dos Eritrócitos (RDW) em eqüinos Puro Sangue Inglês (PSI) submetidos a exercícios de diferentes intensidades - Balarin, Mara Regina Stipp; Lopes, Raimundo Souza [UNESP]; Kohayagawa, Aguemi; Laposy, Cecilia Braga [UNESP]; Fonteque, Joandes Henrique (My University, 2006)
In order to evaluate the influence of exercise of different intensities on Red Blood Cell Distribution width (RDW) and Packed Cell Volume (VG) in Thoroughbred horses, blood was collected from 60 animals, 30 males and 30 females, subdivided in groups of horses with 24 to 36 months of age and not in training, and after 12 months of training, and horses with 36 to 48 months of age in training. Blood samples where collected before and after trot and gallop. Samples where analyzed with a automatic cell counter (Cell-Dyn 3500R, Abbott Diagnostic). Red Blood Cell Distribution width (RDW) values increased significantly after trot and gallop demonstrating a variation in the size of red blood cells, while Packed Medium Cell Volume (VGM) values did not show variations before or after exercise.
Values of Red Blood Cell Distribution Width (RDW) in thoroughbred horse submitted to exercise of different intensity
Keywords: Cell- Dyn 3500R; Horses; Red blood cell distribution width (RDW); Thoroughbred; Animalia; Equidae